The teaching of urban geography: challenges and practices for teachers of Geography / O ensino da geografia urbana: desafios e práticas para os professores de Geografia - Reynaldo Daivyd Lopes da Silva (Universidade Estadual de Alagoas, 2019)
The main issues addressed are the problem of the teaching of urban geography being a fundamental variable for the cognitive development of children in relation to the urban space. The lesson project addresses the challenge associated with teaching urban geography and assisting teachers in geography. The methodology used is based initially on the study of works that involve a theme. The data samples were applied to informative questions and answers in order to clarify the particularities of the studied object. It was necessary to use tokens to facilitate the theoretical basis and re-readings. The indicators point to the existence of a challenge as teaching practices in geography. These problems were found in a failure of teachers with the theme added to the lack of appropriate pedagogical resource. Observe as the main teaching stations become necessary improvements, technological and consider the creation of laboratories geography. It is concluded that urban geography in geography classes can create tasks to work the reality and the daily life of a reflection on the formation of the urban environment. As for them, the challenges are overcome and require investment and planning to meet the demands.